Non-bank dealing and liquidity bifurcation in fixed-income markets - Michael Brolley; David A. Cimon (Bank of Canada, 2025)
Non-bank financial institutions, such as principal-trading firms and hedge funds, increasingly compete with bank-owned dealers in fixed-income markets. Some market participants worry that if non-bank financial institutions push out established bank dealers, liquidity will become unreliable during times of stress. We model non-bank entry and state-dependent liquidity provision. Non-bank participants improve liquidity more during normal times than in stress, leading to a bifurcation of liquidity. In the cross-section, their entry improves liquidity for large and previously unserved small clients; however, banks may no longer provide reliable liquidity to marginal clients. Central bank lending may limit harmful bifurcation during times of stress if that lending is predictable and at sufficiently favourable terms.
Keywords: G10; G20; G21; G23; L10; L13; L14; 330; Economic models; Financial institutions; Financial markets; Market structure and pricing